Respuesta :
A)un+1-un=d
3(n+1)-2 -3n+2
3n+3-2-3n+2
=3 (since it's a costant this means that the sequence is arithmetic)
B)we already found d which equals 3
u1 equals 3*1-2 which equals 1(substitute 1 into the formula)
so u2 equals either 1+3 =4
or 3*2-2 which also equals 4
P.S the number next to n is always equal to d ,if you get d as a form of n+,- a number then it's not arithmetic,if it was a constant then it is arithmetic
hope this helps :)
3(n+1)-2 -3n+2
3n+3-2-3n+2
=3 (since it's a costant this means that the sequence is arithmetic)
B)we already found d which equals 3
u1 equals 3*1-2 which equals 1(substitute 1 into the formula)
so u2 equals either 1+3 =4
or 3*2-2 which also equals 4
P.S the number next to n is always equal to d ,if you get d as a form of n+,- a number then it's not arithmetic,if it was a constant then it is arithmetic
hope this helps :)
[tex]U_n = 3n-2\\\\ \Longrightarrow~~\boxed{U_1 = 3\times 1 -2} = \boxed{1}[/tex]